Hemidiaphragm work in large pleural effusion and its insignificant impact on blood gases: a new insight based on in silico study - Gólczewski, Tomasz; Stecka, Anna M.; Grabczak, Elżbieta M.; Michnikowski, Marcin; Zielińska-Krawczyk, Monika; Krenke, Rafał (Frontiers in Physiology, 2025)
ObjectiveComputer simulations, enabling observations of variables inaccessible in living patients, provide a powerful approach to studying complex physiological phenomena. This in silico study presents the use of a virtual patient to investigate the impact of large pleural effusion (PE) and therapeutic thoracentesis (TT) on hemidiaphragm function and arterial blood gases.MethodsInspired by unexpected phenomena observed in living patients undergoing large-volume TT, we formulated four questions regarding this impact. To answer these questions, we simulated right-sided PE in our virtual patient and studied changes in the pleural pressure in the ipsilateral hemithorax (Ppli) and lung volume during the respiratory cycle (exemplified by Ppli-V loops, where V is the volume of both lungs), airflows in the main bronchi, and alveolar O2 (PAO2) and CO2 (PACO2) partial pressures.ResultsSimulations highlighted that: (a) mediastinal compliance critically affects hemidiaphragm work; (b) the 8-shaped Ppli-V loops are associated with hemidiaphragm inversion, where exhalation from the ipsilateral lung occurs during a part of both the inspiratory and expiratory phases, and vice versa; (c) pre-TT PAO2 may be elevated due to reduction of the tidal volume to end-expiratory lung volume ratio; and (d) pre-TT Ppli amplitudes during respiration can exceed post-TT values when mediastinal compliance is high.ConclusionOur findings emphasize the significance of mediastinal compliance in pleural effusion physiology and suggest insignificant influence of the ipsilateral hemidiaphragm inverted due to large PE on arterial gas tensions. This study underscores the utility of virtual patient models for elucidating unexpected physiological behaviors and optimizing clinical interventions.